Acupuncture Treatment in Patient with Uterine Polyp - Zhu, Prof Dr Jihe; Arsovska, BSc Blagica; Kozovska, BSc Kristina (International Journal of Innovative Research in Medical Science, 2018)
Uterine polyps are benign growths on the inner wall of the uterus, which extend into the uterine cavity. Excessive growth of the mucous membrane of the uterus (endometrium) leads to the formation of polyps on the uterus. Uterine polyps are usually non-cancerous (benign), although some may be carcinogenic or possibly develop over time into cancer. Polyps can be divided into two groups: endo-cervical polyps and endometrial polyps. Uterine polyps most commonly occur in women who undergo menopause or are in postmenopausal period, although polyps may occur in younger women too. In Traditional Chinese Medicine (TCM), the cause for uterine polyps is usually a combination of Blood deficiency, Blood stagnation and Liver/Kidney Deficiency. The aim of the treatment is to move the blood, to make the blood flow free and smooth, resolve the dampness, resolve the blood stagnation, treat the underlying deficiencies and etc. The treated patients is 41 year old woman, diagnosed with 10 mm uterine polyp. The patient was also diagnosed with infertility and was having irregular periods. The patient was treated with acupuncture in a clinic for TCM and acupuncture in Skopje. In a period of 4 months, 14 treatments were made, indoor, on a room temperature, with duration of the treatments of 30-45 minutes. After the 4th treatment her period was regularized and after 14 treatments the polyp was gone. Acupuncture as a treatment for uterine polyps is safe and effective treatment and gave very satisfying and positive results in our treated patient.